Association between plasminogen activator inhibitor‑1 (PAI-1) 4G/5G polymorphism and circulating PAI-1 level in systemic lupus erythematosus and rheumatoid arthritis: A meta-analysis - Bae, S.-C.; Lee, Y. H. (Zeitschrift für Rheumatologie, 2020)
Objective This study systemically reviewed the evidence regarding the association between plasminogen activator inhibitor‑1 ( PAI‑1 ) 4G/5G polymorphism and susceptibility to systemic lupus erythematous (SLE)/lupus nephritis (LN) and rheumatoid arthritis (RA) and the relationship between circulating PAI‑1 levels and SLE/LN and RA. Methods We conducted a meta-analysis on the association between the PAI‑1 4G/5G polymorphism and SLE/LN or RA risk and serum/plasma PAI‑1 levels in patients with SLE/LN and RA and healthy controls. Results Nine articles including 657 patients with SLE and 668 controls and 567 patients with RA and 772 controls were included. No association was revealed between SLE and PAI‑1 4G allele in all study subjects (odds ratio [OR] = 0.944, 95% confidence interval [CI] = 0.808–1.102, p = 0.463). Ethnicity-based stratification showed no association between the PAI‑1 4G allele and SLE among Europeans and Asians. No association was detected between LN and RA and the PAI‑1 4G allele (OR = 0.886, 95% CI = 0.713–1.102, p = 0.278; OR = 0.8736, 95% CI = 0.747–1.020, p = 0.088, respectively) or between SLE/LN and RA and the PAI‑1 4G/5G polymorphism using the recessive and dominant models and homozygote contrast. The circulating PAI‑1 level was significantly higher in the SLE group than in the control group (standardized mean difference [SMD] = 0.337, 95% CI = 0.057–0.619, p = 0.019). However, serum/plasma PAI‑1 level showed no significant difference between RA and control group (SMD = 0.333, 95% CI = −0.6989–1.35, p = 0.527). Conclusions There was no association between the PAI‑1 4G/5G polymorphism and SLE/LN and RA development and significantly higher levels of circulating PAI‑1 were observed in patients with SLE but not in those with RA.